Random skin biopsy of patients with intravascular large B‐cell lymphoma associated with thrombocytopenia and coagulation abnormalities: Proposal of a modified biopsy method. Issue 3 (30th December 2014) - Maekawa, Takeo; Komine, Mayumi; Murata, Satoru; Fukushima, Noriyoshi; Ohtsuki, Mamitaro
Abstract Intravascular large B‐cell lymphoma (IVLBCL) is classified as a rare type of non‐Hodgkin's B‐cell lymphoma by the World Health Organization. It is characterized by the presence of lymphoma cells in the lumens of the small vessels of several organs, most notably the skin. Diagnosis of IVLBCL is difficult because of the lack of lymphadenopathy and because lesions need to be histologically confirmed via a biopsy of the affected organs. Random skin biopsy (RSB) of normal‐appearing skin is a useful and apparently safe means of evaluating IVLBCL. However, patients with IVLBCL often exhibit thrombocytopenia, and we describe a case in which a patient with thrombocytopenia experienced hemorrhagic shock and died shortly after RSB. For this reason, we reviewed cases of RSB performed at our hospital and found that the middle adipose tissue contained a higher percentage of atypical lymphoid cells than other layers of the skin. On the basis of our findings, we propose a strategy for the safer performance of RSB in IVLBCL patients with thrombocytopenia and coagulation abnormalities.